Female homicides and femicides in Ecuador: a nationwide ecological analysis from 2001 to 2017 - Esteban Ortiz-Prado; Paola Villagran; Ana Lucia Martinez-Abarca; Aquiles R. Henriquez-Trujillo; Katherine Simbaña-Rivera; Lenin Ana M. Gómez-BarrenoDiaz; Carla E. Moyano; Vanessa Arcos-Valle; Maria Dolores Miño; Sara A. Morgan (BMC, 2022)
Abstract Background Gender-based violence is a major public health concern arising from the structural discrimination of women and girls. In 2014, Ecuador criminalized acts of femicide in response to a growing crisis across the region. As no epidemiological studies on the state of female homicides and femicides have been published, we estimated patterns of female homicides and femicides nationally and the burden through economic cost per years of life lost, between 2001 and 2017. Methods Using aggregated data from the National Institute of Census and Statistics and police records we estimated the annual mortality rates, cumulative incidence and prevalence odds ratios for female homicides and femicides, from 2001 to 2017. The impact of aggressions, assaults and violence on years of life lost due to premature mortality was estimated using the Human Capital method. Results Over the period, at least 3236 cases of female homicides and femicides were reported. The highest murder rate occurred in the province of Sucumbíos (6.5 per 100,000) and in the Putumayo canton (12.5 per 100,000). The most common way to murder their victims was using firearms (38%). The highest odds ratio was estimated for women aged between 25 and 29, at 4.5 (3.9-5.1), of primary school attainment at 17.2 (14.6-20.3) and of Afro-Ecuadoran descent 18.1 (10.5-30.9). Female homicide-related costs reached, on average, $35 million per year and more than $500 million lost from 2001 to 2017. Conclusions The high rates, distribution and cost indicate that investments are urgently needed to address the structural causes and reduce the impact of female homicides and femicides in Ecuador; thereby protecting the livelihood and well-being of their women and girls.